Wykorzystanie metody rekurencyjnego podziału do identyfikacji grup ryzyka operacyjnego pacjentów z chorobą wieńcową - Misztal, Małgorzata (The Use of Recursive Partitioning Method to Identify Operative Risk Subgroups Among Patients with Coronary Artery Disease, 2005)
The decision to perform Coronary Artery Bypass Grafting (CABG) surgery on a patient with coronary disease is taken under conditions of risk and uncertainty. In that case the benefits of CABG must be balanced against its risk. The study was conducted to identify preoperative risk factors associated with morbidity outcome among patients undergoing isolated CABG and to develop some classification rules assigning patients to selected risk subgroups. Prediction rules were established on the basis of tree-structured models. The following tree- based algorithms were used: QUEST, CRUISE, LOTUS and PLUS.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 330-338